TELAAH SOSIOLOGI HUKUM TERHADAP FENOMENA TALAK DI LUAR PENGADILAN AGAMA - Fatahuddin Aziz Siregar (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2023)
The purpose of this study is to examine the phenomenon of divorce that occurs outside the Religious Courts, especially in Bangun Purba Village. Then describes the practice of divorce in the Bangun Purba community in terms of Sociology of Law. While this type of research is field, which uses a qualitative approach. While the primary data collection methods, namely observation, interviews and documentation. To examine more deeply, researchers use legal system theory which is categorized into three types, namely legal substance, legal structure and legal culture. The results of this study indicate that the occurrence of divorce outside the Religious Courts was caused by ordinary matters and was not questioned by positive law. In addition, according to three respondents, the method of divorce that was carried out was familial (custom), namely through intermediaries, and partly witnessed directly by their respective families.